Kepemimpinan Digital dalam Pendidikan: Sebuah Analisis Bibliometrik - Erna Kusumawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2023)
This study aims to hide developments from published research on digital leadership. This research aims to provide an overview of the topic of digital leadership so that it can provide input regarding the novelty of research in the field of digital leadership. publish This research uses the bibliometric method, namely a literature study that looks at statistics on a publication. The publication database used in this study is Google Scholar with a publication period from 2012 to 2022. To assist researchers in collecting bibliographic data, researchers use the Publish or Perish application. From the research results, 455 articles were obtained which were then processed using the MS Excel and VOSviewer applications. The results of this study indicate that research on digital leadership continues to increase every year, this is also in line with the citation rate which continues to increase before finally dropping in 2020 to 2022. Based on the research results, researchers found that there has been no in-depth research between digital leadership and school management. Directly, which can be seen in terms of quality, satisfaction, digital services and supervision that may be carried out by the heads of educational institutions.